Land Tenure for Social and Economic Inclusion in Yemen : Issues and Opportunities - World Bank (Washington, DC, 2013)
The report, Land Tenure for Social and Economic Inclusion in Yemen: Issues and Opportunities was completed in December 2009. The report addresses the problems of land ownership in Yemen and the various social and economic problems associated with the system of land ownership. Property rights under Yemeni Law are expressed both in custom and statute, but both are informed by shari a (Islamic law), which provides the basic property categories for land in Yemen. There are unfortunately no reliable official statistics for the amount of land within these categories, or how much arable land (a small percentage of total land area) falls within each. It is clear however that certain groups suffer from disadvantages in accessing land and land rights. Daughters are disadvantaged by shari a rules which limit their inheritance shares to only half that of a son. Youth, unable to inherit until the demise of their parents and lacking the capital to buy land, lack access to land and other employment opportunities, which endangers social stability. There are occupational castes (artisans) who are discriminated in land holdings and ethnic minorities, former slaves and immigrants from East Africa, who lack access to land, and especially land ownership, limiting them to the most menial labor. Amongst the recommendations the report addresses are; the law on state land and compulsory acquisition of land by the state are relatively recent and are in general in line with current best practices. There is however some fundamental problems in its legal delineation of state land. First and foremost, there is a need to provide a clearer distinction between state and communal land. In addition, it is clear that implementation of the law concerning state land is badly flawed, and that there are abuses in terms of uncompensated land takings and illegal appropriations of state lands for private purposes. The law concerning private ownership of land is satisfactory in most respects. Yemen has a long tradition of private ownership and land and rental markets. Those markets are clearly quite active, at least in areas where the economic basis for such market activity exists. The right of pre-emption in Yemeni law, a shari a institution, has been criticized by some commentators, but more recent scholarship recognizes its value. Waqf may offend the economic sensibilities of market economists in that waqf land is permanently held out of the land (sales) market, but it does move in rental markets and in the circumstances of Yemen it performs strong social functions. It supports important public functions and provides access to land for the poor but is increasingly negatively affected by weak supervision and corrupt practices. Tenancies are an important means of access to land in Yemen, especially for the poor, and their relatively stable terms stable terms under customary rules have historically provided a reasonable degree of tenure security. Post-land reform issues remain a problem in the southern governorates. Improving the system for recording of land rights has been a focus of law reform discussions in Yemen in recent years. Women are clearly disadvantaged by the terms of inheritance law, and even more greatly disadvantaged by the failure in practice to realize their limited rights under that law. The situation of disadvantaged ethnic groups deserves priority attention. Their lack of secure access to land, especially owned land, is a violation of the humanitarian values of Islam and condemns them to continuing poverty. There is growing competition for land. This is driven in some parts of the country by the development of new water technologies which have enabled larger- scale cultivation and created economic opportunities. It is clear that land dispute resolution mechanisms are not functioning well.